Amplitude analysis and branching fraction measurement of B+ → D∗−D+ s π+ decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2024)
The decays of the B+ meson to the final state D∗−D+ s π+ are studied in protonproton collision data collected with the LHCb detector at centre-of-mass energies of 7, 8, and 13TeV, corresponding to a total integrated luminosity of 9 fb−1. The ratio of branching fractions of the B+ → D∗−D+ s π+ and B0 → D∗−D+ s decays is measured to be 0.173 ± 0.006 ± 0.010, where the first uncertainty is statistical and the second is systematic. Using partially reconstructed D∗+ s → D+ s γ and D+ s π0 decays, the ratio of branching fractions between the B+ → D∗−D∗+ s π+ and B+ → D∗−D+ s π+ decays is determined as 1.31±0.07±0.14. An amplitude analysis of the B+ → D∗−D+ s π+ decay is performed for the first time, revealing dominant contributions from known excited charm resonances decaying to the D∗−π+ final state. No significant evidence of exotic contributions in the D+ s π+ or D∗−D+ s channels is found. The fit fraction of the scalar state T∗ c¯s0(2900)++ observed in the B+ → D−D+ s π+ decay is determined to be less than 2.3% at a 90% confidence level.
*The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, L. Witola, Y. Zhao, A. Zhelezov [und sehr viele weitere Personen]
Gesehen am 10.09.2025
Im Titel sind die Pluszeichen, das Minuszeichen und das Tropfensternchen [ast] hochgestellt sowie der Buchstabe "s" tiefgestellt